2018
DOI: 10.1111/pde.13419
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events reported to the Food and Drug Administration from 2004 to 2016 for cosmetics and personal care products marketed to newborns and infants

Abstract: Pediatric dermatologists should consider submitting cosmetics and personal care product adverse event reports and encouraging consumers to do so likewise in situations in which a product adversely affects a child's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
8
0
4
Order By: Relevance
“…Meanwhile, the incidence of adverse cutaneous reactions to skin care products has also been increasing, particularly over the last 5 years. 1,2 Moreover, recent studies have indicated that even branded skin care products can cause severe adverse cutaneous reactions. 3 Although eczematous reactions account for 90% of these adverse reactions, 4 a link between skin care products and an increased risk of breast cancer has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the incidence of adverse cutaneous reactions to skin care products has also been increasing, particularly over the last 5 years. 1,2 Moreover, recent studies have indicated that even branded skin care products can cause severe adverse cutaneous reactions. 3 Although eczematous reactions account for 90% of these adverse reactions, 4 a link between skin care products and an increased risk of breast cancer has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…A previous analysis of the CAERS database also showed the highest percentage of serious AEs (ie, death, serious injury, hospitalization) reported by consumers was due to baby products . The majority of these adverse events were due to skin reactions and many events led to health care visits . The decreased barrier function, increased infection risk, and a rising concern of allergic contact dermatitis in the neonatal and pediatric population suggest the need for greater caution in this cohort…”
Section: Discussionmentioning
confidence: 93%
“…For these reasons, cosmetic/cosmeceutical effectiveness and safety must be controlled in vitro on cell cultures and in vivo on skin (healthy or affected by minor disorders or mild abnormalities) by methodologies scientifically and clinically correct [12,13]. In reality, although the frequency of cosmetic adverse serious events reported by EU and USA guidelines seems to be low [14,15], the cross allergy and human sensitization phenomena connected with the activity of preservatives, emulsifiers, flavoring, colors, and other chemicals used for cosmetic, food, household, and professional products are increasing worldwide with the risk of chronic diseases [16]. What is interesting to underline on the class of preservatives more often present in many consumer products is that on the one hand, the mass media daily war against the 4-hydroxy benzoic acid and its derivatives, known as parabens, also if they are commonly found in various vegetable foods such as onion, carrots, peaches, etc., and posing a negligible risk to endocrine systems [17,18], and on the other hand, the great use and consume of the thiazolinone derivatives, biologically dangerous chemicals (almost unknown to mass media and consumers), which have provoked many allergic phenomena worldwide [19][20][21].…”
Section: Cosmetic Productsmentioning
confidence: 99%